EVALUASI PROGRAM PEMBERDAYAAN USAHA GARAM RAKYAT DI KECAMATAN PANGENAN, KABUPATEN CIREBON, JAWA BARAT - Nandang A. Deliarnoor; Rd. Ahmad Buchari; Liiklai K. Felfina (Responsive: Jurnal Pemikiran Dan Penelitian Administrasi, Sosial, Humaniora Dan Kebijakan Publik, 2018)
ABSTRACTThe issue of salt production in Indonesia and to fulfill the increasing demand of salt every year through salt import, is the basis of the study. To increase productivity and quality, and the welfare of salt formers, Indonesian government has intervened through enactment of People Salt Business Empowerment Program (PUGAR) in 2011. Even with implementation of the program, problems of national salt still continue, hence there is a need to evaluate the program. The title of the study is Evaluation of PUGAR Program in Pangenan Sub-district, Cirebon District, West Java.The methodology in this study used qualitative hybrid approach, with primary data collection from direct interviews, field observation and secondary data from documents and literature on PUGAR. Evaluation of PUGAR program used evaluation goal-based and logic model, and used William Dunn’s evaluation criteria of effectiveness, efficiency, responsiveness and appropriateness as evaluation tool. The study result shows that evaluation of PUGAR program in Pangenen Sub-district, Cirebon District has been implemented in accordance to the applied standard and guidelines, but it has not met the aspect of effectiveness in its organization and forming of people salt , efficiency of Community Direct Aid  (BLM) policy to help salt farmers, responsiveness in the use of technology and appropriateness to the policies on Spatial Planning of Cirebon District and on salt import, Further in-depth study on the program is still needed.